Modern problems of efficiency of the implementation of innovative projects - Yessengeldina, A.S.; Sitenko, D.A. (KSU Publ., 2016)
The article considers the topical issues of realization of innovative projects in the Republic of Kazakhstan. The attention is focused on the provision at the enterprise of integrated activities for all types of innovation. Criteria of typology of innovative projects are investigated. It emphasizes the role of classification features of projects for the effective management of innovative projects. The main attention is paid on the JSC «National Agency for Technological Development», which supports innovative projects through the provision of innovative grants. The recommendations for the effective management of innovative projects using a project approach are offered.
Инновациялық жобаларды тиімді жүргізудің қазіргі мəселелері
Современные проблемы эффективности реализации инновационных проектов
Keywords: innovation; design approach; innovative project; innovative grant; effectiveness; classification features